SOFA 2001 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
State of Food and Agriculture 2001 Rome, 2001, 322 pp. + CD-ROM ISBN 92-5-104600-X US$49 Euro 53.75